TWO-PHASE FRICTION FACTOR IN GAS-LIQUID PIPE FLOW - Ortiz-Vidal, L. E.; Mureithi, N.; Rodriguez, O. M. H. (Revista de Engenharia Térmica, 2014)
An improved friction factor prediction model for two-phase gas-liquid pipe flow is proposed. The model is based on a previous no-slip formulation where a mixture Reynolds number was defined. In this study, the mixture Reynolds number is modified by introducing slip-ratio information through the inclusion of void-fraction and flow-pattern dependent models. An experimental database reconstituted from the available literature and new frictional pressure-drop data for air-water horizontal flow in an I.D. 0.0204m pipe are also presented. The full database considers several different flow conditions for horizontal two-phase flow of refrigerants and air-water mixtures. It was compared to predictions of models from the literature as well as the new proposed model. We found that the proposed and Müller-Steinhagen-and-Heck methods provide better agreement for the current experimental database. It is shown that the inclusion of void-fraction information on the previous mixture Reynolds definition improves the friction-factor prediction